(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study was conducted with the objective to formulate video assisted teaching programme regarding stem cells and cord blood banking, to assess the pre-test and post-test knowledge score regarding stem cell and cord blood banking among pregnant women , to assess the effectiveness of video assisted teaching programme and to find out the association between pre-test knowledge score with selected socio- demographic variables . The study design was an pre-experimental, one group pre-test post-test research design,60 pregnant women who fulfil the inclusive criteria were selected based on non-probability purposive sampling, after getting informed consent from the study participant, the video assisted teaching programm was administered at Lal Bahadur Shastri Hospital Supela Bhilai (C.G). The study findings revelled that pre- test score of the majority of pregnant women had average knowledge score were61.66%and 36.66%had good knowledge score , post-test majority 90% sample were excellent, 10% sample were good knowledge. Pre-test mean score were 19.35 and SD is 3.64 the post-test were 34.75 and SD is 2.87. The t-value 2.02 which is highly significant at >0.05 which proves the effectiveness of the video assisted teaching programme.